PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PERBANKAN DI INDONESIA - Mulia Andirfa; Irfan; Hikalmi (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2022)
This study aims to examine the effect of capital structure and firm size on thevalue of banking firms in Indonesia. The data used in this study is secondary data asmany as 32 samples by accessing the official website of the financial services authorityusing a purposive sampling method. The method used to analyze the independent variableand the dependent variable is the multiple linear regression method and the classicalassumption test. The results of the study partially that capital structure has no effect onthe value of banking firms in Indonesia for the 2017-2020 period and firm size has asignificant effect on the value of banking firms in Indonesia for the 2017-2020 period.Simultaneously shows that the capital structure and size of the company have asignificant effect on the value of banking companies in Indonesia for the 2017-2020period.